La evolución del Marco jurídico de la protección internacional a refugiados en el Ecuador 2008-2015 - Troncoso Heredia, Manuel Orlando (2016)
This paper is devoted to a study of the legal framework of the Republic of Ecuador concerning migrants and refugees in particular. International and regional documents that address this issue, concretely the 1951 Convention and its 1967 Protocol, the Declaration of Cartagena de Indias 1984 and finally the Brasilia Declaration of 2014 are analyzed Ecuadorian constitution adopted in 2008, analyzed also in this study, it defends international migration as a right of every citizen. Refugees and migrants arriving in this country under certain circumstances, have their human rights guaranteed by the Constitution and particularly by the Executive Decree 1182, discussed in chapter three of the research establishes the duties that contract these people with the country host. The overall objective of this paper is to analyze the evolution of the current legal framework in Ecuador in relation to the protection and human rights of refugees, in line with regional and international instruments in this regard, during the stage 2008 - 2015. Research answers the question: What have been the changes in the legal framework of Ecuador in relation to the protection and human rights of refugees in the stage of 2008-2015, in line with the requirements of regional and international legal instruments in this regard? The work consists of four chapters, the first three are discussed in depth the legal issue of asylum in the world, in Latin America, particularly in Ecuador. Chapter four is devoted to the conclusions and recommendations, where it emphasizes the superiority of the Ecuadorian legal framework and public policies regarding refugees in step 2008-2015 further suggestions are made in order to improve the study of this theme.